Plate osteosynthesis of midshaft clavicle fractures in adolescent contact sports athletes - adolescent clavicle fracture. Issue 1 (24th September 2020) - Kamaci, Saygin; Bess, Laura; Glogovac, Georgina; Colosimo, Angelo J.
Abstract : Surgical treatment of mid-shaft clavicle fractures via anatomical plates in adult athletes is documented to be safe and effective. Functional and cosmetic outcomes in adolescent contact sports athletes have not been well documented. Adolescent athletes (age 11–19) surgically treated for mid-shaft clavicle fractures between 1 May 2011 and 30 October 2017 were included in this study. Twenty-one adolescent athletes with a mean follow-up of 44 months were reviewed. Retrospective chart reviews were performed. Functional and cosmetic outcomes, return to sports time/rate were analyzed using Nottingham Clavicle Scores and a 'Custom Questionnaire'. Return of function and healing, evidenced on radiographs, was achieved in all 21 patients. All patients returned back to competitive sports. The mean time to return back to training was 45.9 ± 16 (24–76) days. Sixteen (76.1%) of the patients reported Nottingham Clavicle Scores with a mean score of 91.7 (85–98). In the Custom Questionnaire, 16 patients who participated in the phone interview were satisfied with the cosmetic outcomes. The most common complaint was implant prominence and irritation in 6 (40%) patients, subsequently requiring implant removal in 3 (18.8%). Surgical fixation of mid-shaft clavicle fractures can lead to excellent union and cosmetic outcomes and a rapid return to sports in adolescent contact sport athletes. However, one should consider the outcomes of implant-related complaints and the possibility of implant removal surgery in the future.